Study on the evolution of discharge times on electrical contact properties of Ag-V2AlC composite material - Huang, Xiaochen; Ge, Jinlong; Zhou, Zijue; Hong, Junyang; Zhang, Dabao; Xu, Tianle (Frontiers in Materials, 2025)
An Ag-20 vol.% V2AlC composite material was prepared using the spark plasma sintering method. The influence of the number of arc discharge on the electrical contact performance of Ag-V2AlC composites was systematically investigated. For the first time, we observed that the arc ablation mechanism evolves with increasing discharge cycles. During single arc ablation, the arc preferentially discharges the Ag phase owing to its lower work function. This process creates a relatively flat ablation region where the V2AlC reinforcement and Ag matrix remain distinct. The V2AlC phase acts as a pinning agent within the Ag matrix, effectively suppressing material splatter. After 10 discharge cycles, the ablation edge of the Ag-V2AlC material develops a mountain-like morphology. This structure prevents material splashing and results in no pores or splatter on the surface. The phase boundary between V2AlC and Ag becomes less distinct, while the breakdown current stabilizes between 19.9 A and 24.1 A. Concurrently, the breakdown strength fluctuates within 4.3 × 106 V/m to 8.2 × 106 V/m. Following 100 discharge cycles, the Ag and V2AlC phases are no longer distinguishable in the ablation area. Micro-protrusions form in the central ablation region, enhancing the local electric field and ultimately reducing the breakdown strength. As discharges increase further, the concentration of low-work-function oxides (V2O5, Al2O3, and Ag2O) rises. These oxides dominate the arc discharge process, further diminishing the breakdown strength. Consequently, the breakdown strength exhibits a three-stage decreasing trend. Although the ablation area expands with discharge cycles, oxide formation increases the molten pool viscosity, preventing significant splatter at the ablation edge. These findings provide a theoretical foundation for designing novel electrical contact materials with enhanced performance.